BOOK REVIEW OF LEAP OF FAITH BY DANIELLE STEEL - Nuraina, Yessi Tifa (LANTERN (Journal on English Language, Culture and Literature), 2015)
Leap of Faith is a novel by a famous novelist Danielle Steel. Leap of Faith debuted at the New York Times and is listed as the best-selling novel to fifty-two of Danielle Steel. This novel is about a girl from France, she is Marie-Ange Hawkins who lives in a magnificent castle name, Chateau de Marmouton. At the castle, she has childhood like everyone's dream. She has the freedom, security and abundant affection of both parents and her brother. But when Marie-Ange Hawkins is eleven years old, a tragic accident that befell his parents take her happiness. She becomes an orphan and is sent to America to live with a cruel aunt of her father. Alone in a foreign land, Marie-Ange Hawkins becomes slave of agricultural land by her aunt, only her friendship with Billy and her dream to return to the castle of her childhood memories that make Marie-Ange endures. But the magic happens when Marie-Ange is 21 years old. She makes it back to the castle Chateau de Marmouton again and even get a chance to be the hostess which is the new owner of the castle, Comte Bernard de Beauchamp proposed her. But behind his proposal, Comte Bernard de Beauchamp keeps his hidden bad intentions to Marie-Ange Hawkins. In desperation and uncertainty areas around her, Marie-Ange has to find the faith and courage to take her last step to save her love ones and herself. Danielle Steel packed this book with very interesting by a simple writing style and storyline in the 1800s which is different from the usual. This book is quite interesting and deserves to be read as entertainment by teenagers and adults.